PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN PENGGUNAAN, DAN TINGKAT KEPERCAYAAN TERHADAP MINAT PENGGUNAAN OVO PADA MAHASISWA PRODI SASTRA INGGRIS UNIVERSITAS SUMATERA UTARA - Pardede, David Alfredo Million; Sabrina , Hesti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
In an era of globalization characterized by digitalization and modernization, the use of technology, particularly financial technology (fintech) like OVO, increasingly dominates everyday life, including among students. OVO, as one of the most popular digital wallets in Indonesia, offers various conveniences for cashless transactions and has partnered with over 200,000 SMEs. This study examines the influence of perceived benefits, ease of use, and trust on the intention to use OVO among students of the English Literature program at Universitas Sumatera Utara. The findings indicate that perceived benefits have a significant positive impact, while ease of use and trust do not show the expected influence. Overall, these three variables together significantly affect students' intention to use OVO. They contribute 49% to the intention to use OVO, with the remaining variance influenced by other factors not measured in this study